Increasing Students' Motivation by Using Computers - Rodríguez Aura Stella; Niño Rosa; Rojas Carmen (Universidad Nacional de Colombia, 2000)
The lack of motivation in the 9th grade students of Tomás Rueda Vargas School was the objective of this project, so we planned a series of workshops in Microsoft Word to apply in the computer lab. We observed that by working in groups of four in the computer lab, the students did the activities with enthusiasm. It could also be noticed that the workshops were effective in reinforcing English learning.